Legal aspects of the death - Silva, Ricardo Gariba (Medicina (Ribeirao Preto), 2005)
The present work intends to clarify and to enhance the legal aspects of the death for the physician. Physicians, as a result of normative attribution, and of the practical circumstances, normally, certify the death in proper document. The legal consequences of the death are focused, with its importance and correlation with the medical declaration of the death. The physician must be more conscientious of his professional act, and, therefore, be more diligent and always zealous with his practices, because of its effects.